Glass fiber prepreg tape as well as preparation method and application thereof in polyethylene pipeline

By performing rare earth modification and compatibilizer optimization on glass fiber, the problem of insufficient tensile strength and impact strength of glass fiber prepreg belt in polyethylene pipelines is solved, and the high strength and high toughness of the material are achieved.

CN120248468AInactive Publication Date: 2025-07-04ANHUI YUANZHEN ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202510409635.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-07-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing glass fiber prepreg tapes have problems with high tensile strength but insufficient impact strength in polyethylene pipelines, and the interface compatibility between the glass fiber and the polyvinyl matrix is ​​poor, resulting in the material being prone to rupture during impact.

Method used

The glass fibers were modified with lanthanum chloride and combined with 2-cyanoethyltriethoxysilane and dopamine to enhance the surfactivity and dispersion of the glass fibers. At the same time, dibutyl itaconic acid and maleic anhydride were used as compatibility agents to synthesize them with high-density polyethylene to improve interfacial compatibility.

Benefits of technology

The tensile strength and impact strength of the glass fiber prepreg tape are significantly improved, the dispersion and interface interaction of glass fibers in the polyvinyl matrix are improved, and the overall mechanical properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fiber reinforced composite materials, and provides a glass fiber prepreg tape and a preparation method and application thereof in a polyethylene pipeline, the glass fiber prepreg tape comprises the following raw materials by weight: 90-110 parts of a polyethylene matrix, 160-200 parts of modified glass fiber, 1-5 parts of a compatilizer, 0.5-5 parts of an antioxidant, and 0.2-1 part of a flame retardant. The glass fiber prepreg tape provided by the invention has good tensile strength and impact strength, and can be widely applied to polyethylene pipelines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fiber - reinforced composite materials, and particularly to a glass fiber prepreg tape, a preparation method thereof, and an application thereof in polyethylene pipes. Background Art

[0002] With the rapid development of modern industry, the demand for pipes in multiple fields such as municipal water supply and drainage, oil and gas transportation, industrial transportation, and oil and gas transportation is increasing continuously. Traditional metal pipes are gradually replaced by new composite material pipes due to problems such as easy corrosion, large weight, and inconvenient installation. Polyethylene pipes have been widely used in many fields due to their advantages such as good corrosion resistance, flexibility, and low cost. However, the mechanical strength of ordinary polyethylene pipes is relatively low, which limits their application under complex working conditions such as high pressure and large diameter.

[0003] In order to overcome the inherent defects of ordinary polyethylene pipes, the glass fiber prepreg tape obtained by compounding glass fiber and polyethylene matrix through a special impregnation process has advantages such as high strength, high modulus, high temperature resistance, and corrosion resistance. By applying the glass fiber prepreg tape in polyethylene pipes, the mechanical properties such as the tensile strength of the pipes can be significantly improved. Among them, glass fiber is the main reinforcing material of the glass fiber prepreg tape, which has good tensile strength and can provide high strength, high modulus, and good heat resistance. However, glass fiber itself is relatively brittle, so it is prone to brittle fracture when subjected to impact, resulting in certain limitations in its impact strength. In addition, when glass fiber is mixed with polyethylene matrix to prepare glass fiber prepreg, stress concentration points will be formed due to uneven dispersion. These stress concentration points may become weak links when subjected to impact, thus causing the material to be more likely to break.

[0004] Patent CN 103254482A discloses a creep-resistant continuous glass fiber reinforced polyethylene prepreg and a preparation method thereof. The application uses a polyethylene matrix, a creep-resistant modifier, a compatibilizer, an antioxidant and glass fiber as main components to prepare a polyethylene prepreg through a certain process. The present invention selects a solid silane coupling agent as a creep-resistant modifier, so that the polyethylene prepreg obtained in the application has good mechanical properties and creep resistance. However, the application does not solve the problem that the glass fiber is relatively brittle, resulting in poor impact strength, which in turn causes the polyethylene prepreg to be easily broken; Patent CN110511573B discloses a wetting and dispersing enhancer. , prepregs and glass fiber reinforced thermoplastic prepreg tapes. The glass fiber reinforced thermoplastic prepreg tape disclosed in the application is composed of matrix resin, graft compatibilizer, antioxidant, flame retardant, wetting and dispersion enhancer and continuous glass fiber. The design of the wetting and dispersion enhancer effectively enhances the fluidity of the resin particles and allows the inorganic powder and the matrix resin to be fully mixed, thereby enhancing the strength of the material, so that the prepared glass fiber reinforced thermoplastic prepreg tape has good appearance performance and tensile strength. However, the applicant has not considered the problem that the impact strength of the glass fiber has certain defects, which may lead to certain application limitations of the prepared product.

[0005] Therefore, there is an urgent need in the market for a glass fiber prepreg tape that can be used in polyethylene pipes and has good tensile strength and impact strength. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention takes polyethylene as the matrix, adds modified glass fiber and synthesizes a glass fiber prepreg tape with a compatibilizer, an antioxidant and a flame retardant. The glass fiber prepreg tape can be widely used in polyethylene pipes and has good tensile strength and impact strength.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On one hand, the present invention provides a glass fiber prepreg tape, which comprises the following raw materials by weight: 90-110 parts of polyethylene matrix, 160-200 parts of modified glass fiber, 1-5 parts of compatibilizer, 0.5-5 parts of antioxidant, and 0.2-1 parts of flame retardant.

[0009] In some embodiments of the present invention, the polyethylene matrix is ​​high density polyethylene.

[0010] High-density polyethylene has high tensile strength and impact resistance, and can withstand large loads and pressures, so that when it is compounded with glass fiber, it can effectively enhance the overall mechanical properties of the composite material and meet the needs of prepreg tapes in high-strength applications.

[0011] In some embodiments of the present invention, the method for preparing the modified glass fiber comprises the following steps:

[0012] (1) Add lanthanum chloride to absolute ethanol, heat to 65 - 80 °C, stir, add diethylenetriaminepentaacetic acid, stir, and then add ammonium chloride, stir to obtain a rare earth solution for standby;

[0013] (2) Immerse the glass fiber in the rare earth solution of step (1), let it stand for 1 - 2 h, filter, and dry to obtain product 1 for standby;

[0014] (3) Mix 2 - cyanoethyltriethoxysilane and deionized water, stir, add acetic acid, stir, add product 1 of step (2), heat to 55 - 65 °C and maintain for 2.5 - 3.5 h, filter, wash, and dry to obtain product 2 for standby;

[0015] (4) Add product 2 of step (3) to a Tris - HCl buffer aqueous solution, stir while ultrasonically treating, add dopamine, react for 23 - 25 h, filter, wash, and dry to obtain the modified glass fiber.

[0016] In some embodiments of the present invention, the mass ratio of the glass fiber to lanthanum chloride is 1:(0.02 - 0.06).

[0017] Preferably, the mass ratio of the glass fiber to lanthanum chloride is 1:0.04.

[0018] In some embodiments of the present invention, in step (3), the mass ratio of product 1 to 2 - cyanoethyltriethoxysilane is 1:(0.03 - 0.07).

[0019] Preferably, in step (3), the mass ratio of product 1 to 2 - cyanoethyltriethoxysilane is 1:0.05.

[0020] In some embodiments of the present invention, in step (4), the mass ratio of product 2 to dopamine is 1:(0.3 - 0.6).

[0021] Preferably, in step (4), the mass ratio of product 2 to dopamine is 1:(0.3 - 0.5).

[0022] More preferably, in step (4), the mass ratio of product 2 to dopamine is 1:0.4.

[0023] The fiberglass prepreg tape is mainly used as a reinforcing layer in polyethylene pipes to endow the polyethylene pipes with better mechanical properties and mechanical loads. Fiberglass is the main reinforcing material of the fiberglass prepreg tape, which can provide high strength, high modulus and good heat resistance. In particular, fiberglass has good tensile strength, but its impact strength has certain application limitations. The main reasons are twofold. First, fiberglass itself is brittle and prone to brittle fracture when subjected to impact, resulting in relatively low impact strength. Second, when fiberglass is compounded with the polyethylene matrix, it will be unevenly dispersed, which is likely to form stress concentration points, causing the fiberglass prepreg tape to be more easily broken after being impacted, thus reducing the impact strength.

[0024] In order to overcome the above-mentioned application limitations of fiberglass, on the one hand, the applicant prepared a rare earth solution using lanthanum chloride as the main raw material, and immersed the fiberglass in the rare earth solution to achieve the modification of fiberglass by rare earth elements to obtain Product 1. Rare earth elements have a low electronegativity, so after being adsorbed on the surface of fiberglass, they can chemically react with the oxides on the surface of fiberglass to form stable rare earth oxides, thereby improving the tensile strength of fiberglass. Further, the doping of rare earth oxides in fiberglass can change the network structure of fiberglass, improving the toughness of fiberglass to a certain extent, and thus improving the impact strength of fiberglass. On the other hand, the applicant used 2-cyanoethyltriethoxysilane and dopamine to jointly modify Product 1. First, 2-cyanoethyltriethoxysilane was introduced to form a uniform protective film through chemical bonding, enhancing the activity and reactivity of the fiberglass surface to improve the dispersibility of fiberglass in the polyethylene matrix. Then, dopamine was introduced. Dopamine forms polydopamine through self-polymerization reaction. There are various polar groups in the molecular structure of polydopamine that can form hydrogen bond interactions with the polyethylene molecular chains, further effectively improving the dispersibility of fiberglass in the polyethylene matrix and making the interface interaction between fiberglass and the polyethylene matrix better, thereby effectively enhancing the impact strength of fiberglass.

[0025] In some embodiments of the present invention, the preparation method of the compatibilizer includes the following steps:

[0026] Mix maleic anhydride, dibutyl itaconate and diisopropylbenzene peroxide, stir, add high-density polyethylene, mix at high speed, discharge, melt and extrude, and receive the material to obtain the compatibilizer.

[0027] Among them, the mass ratio of maleic anhydride to dibutyl itaconate is 1:(0.3 - 0.8).

[0028] Preferably, the mass ratio of maleic anhydride to dibutyl itaconate is 1:0.5.

[0029] The surface of glass fiber has a certain polarity while polyethylene is a non-polar material. This polarity difference results in poor interfacial compatibility between glass fiber and polyethylene. Although the above applicant modified the glass fiber, and the compatibility between the obtained modified glass fiber and the polyethylene matrix has been improved to a certain extent by the introduction of dopamine, the problem of poor compatibility between the modified glass fiber and the polyethylene matrix still exists due to the limited dosage of dopamine. Moreover, the traditional compatibilizer polyethylene grafted maleic anhydride is volatile, and there is still a hidden danger of insufficient interfacial stability when used in combination with the modified glass fiber.

[0030] In addition to the problem of volatility, the traditional compatibilizer polyethylene grafted maleic anhydride also needs to overcome the problem of low grafting efficiency. To solve the above problems, the applicant unexpectedly found that a certain proportion of dibutyl itaconate and maleic anhydride were used as monomers, and high-density polyethylene was selected as the resin to synthesize the compatibilizer. Selecting the same high-density polyethylene as the resin in the polyethylene matrix of the glass fiber prepreg tape can ensure that the compatibilizer is effectively distributed in the polyethylene matrix. The selection of monomers not only solves the problem of the volatility of maleic anhydride, but also has a high grafting efficiency, and the overall compatibilizer also has good stability, which can effectively improve the compatibility between glass fiber and polyethylene matrix, and further improve the tensile strength and impact strength of the glass fiber prepreg tape to a certain extent. It is speculated that the reason is that dibutyl itaconate is a liquid, which can make the small molecules of maleic anhydride intersperse in the liquid voids, effectively avoiding the problem of the volatility of maleic anhydride and improving the grafting efficiency. Further, there is a certain intermolecular force between maleic anhydride and dibutyl itaconate, which makes the structure of the compatibilizer stable.

[0031] In some embodiments of the present invention, the antioxidant is any one of antioxidant 1010, antioxidant 1076, and antioxidant 168.

[0032] In some embodiments of the present invention, the flame retardant is an intumescent flame retardant.

[0033] On the other hand, the present invention also provides a preparation method of the glass fiber prepreg tape described in the above technical solution, including the following steps:

[0034] S1. Mix the polyethylene matrix, compatibilizer, antioxidant, and flame retardant, stir at 500-600 r / min for 2-3 min, seal, and obtain a mixture for standby;

[0035] S2. Extrude the mixture in step S1 at 200-220 °C, and then film the modified glass fiber preheated at 120-140 °C, cool, and form to obtain the glass fiber prepreg tape.

[0036] On the other hand, the present invention also provides an application of the glass fiber prepreg tape described in the above technical solution in a polyethylene pipe. The polyethylene pipe has a three-layer composite structure, which is a thermoplastic PE layer, a glass fiber prepreg tape, and a thermoplastic PE layer from the inside to the outside.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention uses polyethylene as the matrix, designs and adds modified glass fibers, and synthesizes a glass fiber prepreg tape with a compatibilizer, an antioxidant, and a flame retardant. Through the synergistic effect between the components, it has the characteristics of good tensile strength and impact strength, can be widely used in polyethylene pipes, and has good commercial application value.

[0039] (2) The present invention first modifies glass fibers with a rare earth solution prepared with lanthanum chloride as the main raw material. By doping rare earth oxides, while improving the tensile strength of the glass fibers, the toughness of the glass fibers is also improved to a certain extent. Then, 2-cyanoethyltriethoxysilane and dopamine are used to jointly modify the glass fibers modified by the above rare earth solution, improving the surface activity and reactivity of the glass fibers and the interfacial interaction between the glass fibers and the polyethylene matrix, playing a role in synergistically modifying the dispersion effect of the glass fibers, and thus effectively improving the impact strength of the glass fibers.

[0040] (3) The present invention uses dibutyl itaconate and maleic anhydride as monomers to synthesize a compatibilizer with high-density polyethylene, which has high grafting efficiency and makes the compatibilizer have good stability, thereby improving the tensile strength and impact strength of the glass fiber prepreg tape to a certain extent. Specific Embodiments

[0041] The following will describe the present invention in conjunction with specific implementation schemes. It should be noted that the following examples are examples of the present invention, only used to illustrate the present invention, and not used to limit the present invention. Without departing from the gist or scope of the present invention, other combinations and various improvements within the concept of the present invention can be made.

[0042] In the following examples and comparative examples, except for the modified glass fibers and the compatibilizer, the other compound monomers and related reagents used can be purchased from the market. Among them, the high-density polyethylene has the model of HDPE DMDA8008H and is purchased from Shanghai Yichu Petrochemical Co., Ltd.; the glass fibers are purchased from China National Bluestar (Group) Co., Ltd., with the model of E6DR17-2400-386H; the polyethylene grafted with maleic anhydride is purchased from Shenzhen Lijing Biochemical Technology Co., Ltd.; the intumescent flame retardant is pentaerythritol phosphate.

[0043] Preparation Example 1

[0044] The synthesis method of modified glass fiber A includes the following steps:

[0045] (1) Add 4 g of lanthanum chloride to 100 ml of absolute ethanol, heat to 70 °C, stir for 2 h, add 3 g of diethylenetriaminepentaacetic acid, stir for 1 h, and then add 2 g of ammonium chloride, stir for 2 h to obtain a rare earth solution for standby;

[0046] (2) Immerse 100 g of glass fiber into the rare earth solution in step (1), let it stand for 1.5 h, filter, and dry at 120 °C for 4 h to obtain product 1 for standby;

[0047] (3) Mix 3 g of 2-cyanoethyltriethoxysilane and 30 ml of deionized water, stir for 30 min, add acetic acid to adjust the pH to 3, stir for 15 min, add 60 g of product 1 in step (2), heat up to 60 °C and maintain for 3 h, filter, wash with deionized water, and dry in vacuum at 105 °C for 5 h to obtain product 2 for standby;

[0048] (4) Add 50 g of product 2 in step (3) to 100 ml of Tris-HCl buffer aqueous solution with pH = 8.8, stir while ultrasonically irradiating for 1 h, add 20 g of dopamine, react for 24 h, filter, wash with deionized water, and dry in vacuum at 95 °C for 4 h to obtain modified glass fiber A.

[0049] Preparation Example 2

[0050] For modified glass fiber B, the specific implementation method is the same as that of modified glass fiber A, the difference is that: in step (1), the mass of lanthanum chloride is replaced with 1.5 g.

[0051] Preparation Example 3

[0052] For modified glass fiber C, the specific implementation method is the same as that of modified glass fiber A, the difference is that: in step (3), the mass of 2-cyanoethyltriethoxysilane is replaced with 1.4 g.

[0053] Preparation Example 4

[0054] For modified glass fiber D, the specific implementation method is the same as that of modified glass fiber A, the difference is that: in step (4), the mass of dopamine is replaced with 13 g.

[0055] Preparation Example 5

[0056] The synthesis method of compatibilizer A includes the following steps:

[0057] Mix 10 g of maleic anhydride, 5 g of dibutyl itaconate and 1 g of diisopropylbenzene peroxide, stir evenly, add 50 g of high-density polyethylene, mix at high speed for 3 min, discharge, and extrude at 180 °C, then receive the material to obtain compatibilizer A.

[0058] Preparation Example 6

[0059] Compatibilizer B, the specific implementation method is the same as that of compatibilizer A, the difference is that: the mass of dibutyl itaconate is replaced by 2 g.

[0060] Preparation Example 7

[0061] Compatibilizer C, the specific implementation method is the same as that of compatibilizer A, the difference is that: the mass of dibutyl itaconate is replaced by 9 g.

[0062] Example 1

[0063] A glass fiber prepreg tape, by weight, the glass fiber prepreg tape comprises the following raw materials: 100 parts of high-density polyethylene, 180 parts of modified glass fiber A, 3 parts of compatibilizer A, 3 parts of antioxidant 1010, and 0.6 parts of pentaerythritol phosphate.

[0064] The preparation method of the glass fiber prepreg tape in this embodiment comprises the following steps:

[0065] S1. Mix high-density polyethylene, compatibilizer A, antioxidant 1010 and pentaerythritol phosphate, stir at 550 r / min for 2.5 min, seal, and obtain a mixture for standby;

[0066] S2. Extrude the mixture in step S1 at 210 °C, then apply a film to the modified glass fiber A preheated at 130 °C, cool, and form (thickness is 0.5 mm), thus obtaining the glass fiber prepreg tape.

[0067] Example 2

[0068] A glass fiber prepreg tape, by weight, the glass fiber prepreg tape comprises the following raw materials: 90 parts of high-density polyethylene, 160 parts of modified glass fiber A, 1 part of compatibilizer A, 0.5 part of antioxidant 1076, and 0.2 parts of pentaerythritol phosphate.

[0069] The preparation method of the glass fiber prepreg tape in this embodiment comprises the following steps:

[0070] S1. Mix high-density polyethylene, compatibilizer A, antioxidant 1076 and pentaerythritol phosphate, stir at 500 r / min for 3 min, seal, and obtain a mixture for standby;

[0071] S2. Extrude the mixture in step S1 at 200 °C, then apply a film to the modified glass fiber A preheated at 120 °C, cool, and form (thickness is 0.5 mm), thus obtaining the glass fiber prepreg tape.

[0072] Example 3

[0073] A glass fiber prepreg tape, by weight, the glass fiber prepreg tape comprises the following raw materials: 110 parts of high-density polyethylene, 200 parts of modified glass fiber A, 5 parts of compatibilizer A, 5 parts of antioxidant 168, and 1 part of pentaerythritol phosphate.

[0074] The preparation method of the glass fiber prepreg tape in this embodiment comprises the following steps:

[0075] S1. Mix high-density polyethylene, compatibilizer A, antioxidant 168 and pentaerythritol phosphate, stir at 600 r / min for 2 min, seal, and obtain a mixture for standby;

[0076] S2. Extrude the mixture of step S1 at 220 °C, then film the modified glass fiber A preheated at 140 °C, cool, and form (thickness: 0.5 mm), thus obtaining the glass fiber prepreg tape.

[0077] Example 4

[0078] This embodiment provides a glass fiber prepreg tape and its preparation method. The specific implementation manner is the same as that of Embodiment 1, except that modified glass fiber B is used to replace modified glass fiber A in equal amount.

[0079] Example 5

[0080] This embodiment provides a glass fiber prepreg tape and its preparation method. The specific implementation manner is the same as that of Embodiment 1, except that modified glass fiber C is used to replace modified glass fiber A in equal amount.

[0081] Example 6

[0082] This embodiment provides a glass fiber prepreg tape and its preparation method. The specific implementation manner is the same as that of Embodiment 1, except that modified glass fiber D is used to replace modified glass fiber A in equal amount.

[0083] Example 7

[0084] This embodiment provides a glass fiber prepreg tape and its preparation method. The specific implementation manner is the same as that of Embodiment 1, except that compatibilizer B is used to replace compatibilizer A in equal amount.

[0085] Example 8

[0086] This embodiment provides a glass fiber prepreg tape and its preparation method. The specific implementation manner is the same as that of Embodiment 1, except that compatibilizer C is used to replace compatibilizer A in equal amount.

[0087] Example 9

[0088] This embodiment provides a glass fiber prepreg tape and a preparation method thereof. The specific implementation manner is the same as that of Embodiment 1, except that commercially available conventional polyethylene grafted maleic anhydride is used to replace compatibilizer A in equal amounts.

[0089] Comparative Example 1

[0090] This comparative example provides a glass fiber prepreg tape and a preparation method thereof. The specific implementation manner is the same as that of Embodiment 1, except that glass fiber is used to replace modified glass fiber A in equal amounts.

[0091] Performance testing

[0092] The tensile strength and impact strength of the glass fiber prepreg tapes of the above-mentioned Embodiments 1-9 and Comparative Example 1 were tested, and the test results are shown in Table 1.

[0093] The test reference standard for tensile strength is ISO 527-3;

[0094] The test reference standard for impact strength is ISO 179-2.

[0095] Table 1

[0096] Group Tensile Strength (MPa) Impact Strength (J / M) Example 1 950 95 Example 2 945 98 Example 3 947 97 Example 4 932 88 Example 5 937 84 Example 6 935 85 Example 7 943 93 Example 8 941 90 Example 9 939 89 Comparative Example 1 927 75

[0097] It can be seen from the data in Table 1 that the glass fiber prepreg tapes in Embodiments 1-3 of the present invention generally have good tensile strength and impact strength. Among them, in Embodiments 4-6, the modification ratios of rare earth solution, 2-cyanoethyltriethoxysilane, and dopamine to glass fiber in the synthesis process of modified glass fiber were changed, resulting in poor improvement of the toughness of glass fiber and the dispersibility of glass fiber in the polyethylene matrix, both of which led to a decrease in the impact strength of the glass fiber prepreg tape and had little effect on the tensile strength; in Embodiments 7-8, the ratio between dibutyl itaconate and maleic anhydride in the synthesis process of the compatibilizer was changed, and in Embodiment 9, commercially available conventional polyethylene grafted maleic anhydride was used to replace compatibilizer A in equal amounts, both of which led to a certain degree of decrease in the tensile strength and impact strength of the glass fiber prepreg tape; in Comparative Example 1, glass fiber was used to replace modified glass fiber A in equal amounts, resulting in poor results for both the tensile strength and impact strength of the glass fiber prepreg tape.

[0098] The above embodiments are only for explaining the technical concept and characteristics of the present invention, and the purpose is to enable those who are familiar with this technology to understand the content of the present invention and implement it. It cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A glass fiber prepreg tape, characterized in that, By weight parts, the glass fiber prepreg tape comprises the following raw materials: 90-110 parts of polyethylene matrix, 160-200 parts of modified glass fiber, 1-5 parts of compatibilizer, 0.5-5 parts of antioxidant, and 0.2-1 part of flame retardant.

2. The glass fiber prepreg tape according to claim 1, wherein The polyethylene matrix is high-density polyethylene.

3. The glass fiber prepreg tape according to claim 1, characterized in that, The preparation method of the modified glass fiber comprises the following steps: (1) Add lanthanum chloride into absolute ethanol, heat to 65-80 °C, stir, add diethylenetriaminepentaacetic acid, stir, and then add ammonium chloride, stir to obtain a rare earth solution for standby; (2) Immerse the glass fiber into the rare earth solution in step (1), let it stand for 1-2 h, filter, dry to obtain product 1 for standby; (3) Mix 2-cyanoethyltriethoxysilane and deionized water, stir, add acetic acid, stir, add product 1 in step (2), heat to 55-65 °C and keep for 2.5-3.5 h, filter, wash, dry to obtain product 2 for standby; (4) Add product 2 in step (3) into Tris-HCl buffer aqueous solution, stir while ultrasonically irradiating, add dopamine, react for 23-25 h, filter, wash, dry to obtain the modified glass fiber.

4. The glass fiber prepreg tape according to claim 3, wherein, The mass ratio of the glass fiber to lanthanum chloride is 1:(0.02-0.06).

5. The glass fiber prepreg tape according to claim 3, characterized in that, In step (3), the mass ratio of product 1 to 2-cyanoethyltriethoxysilane is 1:(0.03-0.07).

6. The glass fiber prepreg tape according to claim 3, characterized in that, In step (4), the mass ratio of product 2 to dopamine is 1:(0.3-0.6).

7. The glass fiber prepreg tape according to claim 1, wherein The antioxidant is any one of antioxidant 1010, antioxidant 1076, and antioxidant 168.

8. The glass fiber prepreg tape according to claim 1, characterized in that, The flame retardant is an intumescent flame retardant.

9. A method for preparing a glass fiber prepreg tape according to any one of claims 1-8, characterized in that, Comprises the following steps: S1. Mix the polyethylene matrix, compatibilizer, antioxidant, and flame retardant, stir at 500-600 r / min for 2-3 min, seal to obtain a mixture for standby; S2. Extrude the mixture in step S1 at 200-220 °C, and then film the preheated modified glass fiber at 120-140 °C, cool, and form to obtain the glass fiber prepreg tape.

10. Use of the glass fiber prepreg tape according to any one of claims 1-8 in a polyethylene pipe, characterized in that, The polyethylene pipe is a three-layer composite structure, which is a thermoplastic PE layer, a glass fiber prepreg tape, and a thermoplastic PE layer from the inside to the outside.

Citation Information

Patent Citations

  • Creep resistance continuous glass fiber reinforced polyethylene prepreg tape and preparation method thereof

    CN103254482A

  • Wetting and dispersing reinforcing agents, prepregs and glass fiber reinforced thermoplastic prepreg tapes

    CN110511573B

Cited By

  • Glass fiber prepreg tape and high-strength water supply pipe prepared from same

    CN122103802A